2017
DOI: 10.1038/s41533-017-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Call to action: improving primary care for women with COPD

Abstract: In this perspective-based article, which is based on findings from a comprehensive literature search, we discuss the significant and growing burden of chronic obstructive pulmonary disease in women worldwide. Chronic obstructive pulmonary disease now affects both men and women almost equally. Despite this, there remains an outdated perception of chronic obstructive pulmonary disease as a male-dominated disease. Primary care physicians play a central role in overseeing the multidisciplinary care of women with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
4
32
0
1
Order By: Relevance
“…In summary, more research in sex differences and its implications for therapy is obviously needed [35,36]. However, we speculate that the association of female sex with several treatments in 2014 and not in 2005 could be explained by a higher awareness among physicians of the increased COPD prevalence, mortality and symptom level in women [37]. …”
Section: Discussionmentioning
confidence: 99%
“…In summary, more research in sex differences and its implications for therapy is obviously needed [35,36]. However, we speculate that the association of female sex with several treatments in 2014 and not in 2005 could be explained by a higher awareness among physicians of the increased COPD prevalence, mortality and symptom level in women [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mortality among women due to COPD is higher than from many of the most commonly recognized forms of cancer. 10 In a Swedish study, COPD mortality among women increased during 1999-2009, and life expectancy in the COPD population was 9.4 years lower for women (vs. 7.4 years lower in men) compared with that of the average Swedish population. 13 Several findings also suggested that health status and quality of life is more impaired in women than in men with COPD.…”
Section: Introductionmentioning
confidence: 97%
“…4,5 However, recent studies demonstrated that the prevalence of COPD is similar among men and women. [6][7][8][9][10][11] A study by Mamary et al 12 reported that men were more prone to have underdiagnosis of COPD than women. Furthermore, mortality among women due to COPD is higher than from many of the most commonly recognized forms of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course of inflammatory lung diseases is influenced by several factors including sex, hormones, and poor air quality (Doherty et al 2009;Liptzin et al 2015;Silva et al 2017). Sex differences in lung disease incidence, prevalence, and severity have been noted for years, as well as increased prevalence rates for asthma, chronic obstructive pulmonary disease (COPD), and other inflammatory diseases in women versus men (Fuseini and Newcomb 2017;Tsiligianni et al 2017;Center for Disease Control and Prevention, 2018;Shah and Newcomb 2018). The number of women diagnosed with asthma, bronchitis, emphysema, COPD, pneumonia, and lung cancer has significantly increased in the past decade at higher rates than for men, and the mortality associated with many of these conditions is also now higher for women than men (Martinez et al 2007;Aryal et al 2014;Jenkins et al 2017).…”
Section: Introductionmentioning
confidence: 99%